Chapter Ономастика и Парадокс: Достоевский и крушение онтологической целостности персонажа - Apollonio, Carol (Biblioteca di Studi Slavistici, 2023)
Onomastics and Paradox: Dostoevsky and the Collapse of the Ontological Integrity of Character. Onomastics plays a key role in Dostoevsky's poetics: the names of most of his characters are essential to their portraits, even though these names rarely signify unambiguously. Moreover, a number of his characters are nameless and a semantic tension arises from this absence: the impossibility of "branding" the hero with a name prevents us from identifying his or her features through verbal onomastic symbolism. The portrait of such characters necessarily remains somewhat murky. It is no coincidence that the "nameless heroes" are the most paradoxical and enigmatic characters of Dostoevsky's creative world. By denying them names, Dostoevsky seeks to destroy the inner integrity of these heroes, their identity, in order that a living, independent, and contradictory personality emerges in them.